Perverse leaks: Perverse and stereotyped representations in Juntas Contra Vazamentos campaign - Amaral, Muriel Emídio Pessoa [UNESP]; Filho, Claudio Bertolli [UNESP] (Universidade Estadual de Londrina, 2017)
The purpose of this article is to analyze the intention of advertising in the permanence of stereotypes by the perversion of values, appropriating political and social issues in the imagistic mountings. For this, the research has like empirical object Juntas Contra Vazamentos campaign. The campaign in question objectifies the status of women in the name of promoting a new product on the market, in addition to building the body's fetishization in synesthetic promotion of images that dialogue with the aesthetics of fragrant.
Vazamentos perversos: Representações perversas e estereotipadas na campanha juntas contra vazamentos
Keywords: Advertising; Fetish; Mountings; Perversion